A variant origin of common hepatic, right inferior phrenic artery and accessory right renal artery - Prajna PS; Poonam K (Department of Surgery, UKM Medical Centre, 2011)
A case of variations in the ventral and lateral and dorsal branches of abdominal aorta were observed in a 50-year-old male cadaver during routine dissection for medical undergraduate students. The common hepatic artery was arising directly from abdominal aorta. Right inferior phrenic artery originated directly from the abdominal aorta along with upper right renal artery about 0.4cm below the origin of superior mesenteric artery. Triple renal arteries were seen on the right side, all arising from abdominal aorta whereas on the left side, a single renal artery was seen entering the kidney. The upper right renal artery was present behind the inferior vena cava whereas the middle and inferior right renal arteries were present in front of the inferior vena cava. On the right side, ureter was placed anterior to renal vessels. Knowledge of the above variations in the branches of abdominal aorta have clinical importance not only for surgeons but also for interventional radiologists.